EFEKTIVITAS PEMBERIAN BROWNIS BANGUN-BANGUN (COLEUS AMBONICUS LOUR) TERHADAP PRODUKSI ASI (Jurnal Kesehatan Siliwangi, 2021)
Exclusive breastfeeding for six months is very important for the survival of the child. Many factors influence exclusive breastfeeding for infants aged 0-6 months, namely malnutrition and overnutrition, which also arise as a result of feeding before the baby is 6 months old. The leaves of the wakes have the potential as lactagogues, indicated by the presence of saponins, flavonoids and polyphenols so that they can increase breastfeeding hormones such as prolactin and oxytocin. This study aims to see the effectiveness of giving Bangun-Bangun Brownis (Coleus Ambonicus Lour) on milk production. The research method used is a quasi-experimental research design with one group pretest-postest. with control. The sample was 72 hour post partum mothers (aged 17-40 years) with a purposive sampling technique. Data analysis consisted of univariate analysis with different test with Wilcoxon sign rank test and Mann Whitney test. The results of the research with the Wilcoxon sign rank test showed that there was a significant difference or p-value of 0.001 <0.05 in the volume of breast milk between the volume of milk at the 1st pumping and 15th in the intervention compared to the control group. In the Mann Whitney test, there was a significant difference in breast milk volume where the significance value or p-value was 0.000 <0.05, so there was a significant difference in breast milk volume between the intervention and control groups after treatment. Giving brownis awakening can effective increase breast milk production for breastfeeding mothers and is an alternative breast milk booster.